Characterizing diet quality indicators and their demographic determinants among adults: a population-based study in Northern Ghana - Kolbila, Paula Malebna; Abdul-Samed, Musah; Rahama, Seidu; Apau-Tete, Afia Aboabea; Abugri, Bruce A.; Amoore, Bright Yammaha; Gaa, Patience K.; Mogre, Victor (Frontiers in Nutrition, 2025)
ObjectivesUnhealthy eating patterns increase the risk of non-communicable diseases (NCDs), such as type 2 diabetes, heart disease, and cancer. A healthy diet should provide energy and nutrients for growth, maintenance, activity, and infection prevention. Global indicators include dietary diversity score, following recommended food groups, and NCD-protective consumption. We assessed dietary patterns and associated demographic factors among adult Ghanaians from northern Ghana using indicators aligned with global recommendations for healthy eating.MethodsA cross-sectional design was employed, utilizing a diet quality questionnaire (DQ-Q) to evaluate five indicators: food group diversity score (FGDS), all-5 recommended food groups, NCD-protect scores, NCD-risk scores, and global dietary recommendation (GDR) scores. Data analysis incorporated Spearman's rho, Mann-Whitney, Kruskal-Wallis tests, and multiple linear regression to explore associations.ResultsA total of 842 participants were recruited. In which 96.4% consumed starchy staples, over 90% ate vegetables, and 70% included fruits in their diet. Mean (SD) scores for FGDS, NCD-protect, World Health Organization (WHO) all-five food groups, NCD-risk, and GDR were 10, 9, 5, 8, and 18, respectively. A moderately positive correlation was observed between NCD-protect scores and FGDS (r = 0.763, P = 0.001), as well as with WHO all-five groups (r = 0.688, P < 0.001). Higher education was the strongest predictor of better diet quality—those with secondary education ate more protective foods, had greater dietary diversity, and better WHO-recommended food adherence—while Mole-Dagbani/Gonja ethnicity was consistently associated with poorer diet quality; married/cohabiting status modestly increased both protective and risk food consumption, and each additional year of age slightly reduced NCD-risk food intake.ConclusionConsumption of staple foods was widespread. Vegetables were consumed frequently, but not fruits. Diets were only moderately diverse, and dietary patterns reflecting NCD-risk factors were prevalent. Dietary patterns reflecting NCD-risk factors were widespread. Ethnicity, marital status, and employment status significantly predicted diet quality indicators, informing future dietary guidelines.